FALCIPARUM MALARIA PRESENTING WITH TETANY: ENDOCRINOPATHIES ASSOCIATED WITH FALCIPARUM MALARIA - Aijazi, Ishma; Chaudary, Monazza; Adam Mukhtar, Sara Hussein; Abdulla Al Shama, Fadhil Mustafa (Journal of Ayub Medical College Abbottabad, 2020)
Malaria is a common public health problem which may have high morbidity and mortality. Physicians should be aware of the unusual presentations of this disease so that it can be timely diagnosed and treated. Herein we are presenting a case of falciparum malaria who presented to the hospital with carpopedal spasm and tetany. We will subsequently discuss mineral homeostasis and the mechanisms of hypocalcemia in falciparum malaria and the dysregulation of calcium, phosphorus and magnesium metabolism.